Assessing the Time of Emergence of Marine Ecosystems From Global to Local Scales Using IPSL‐CM6A‐LR/APECOSM Climate‐To‐Fish Ensemble Simulations - Nicolas Barrier; Olivier Maury; Roland Seferian; Yeray Santana‐Falcón; Alex Tidd; Matthieu Lengaigne (Earth's Future)
Abstract Climate change is anticipated to considerably reduce global marine fish biomass, driving marine ecosystems into unprecedented states with no historical analogs. The Time of Emergence (ToE) marks the pivotal moment when climate conditions (i.e., signal) deviate from pre‐industrial norms (i.e., noise). Leveraging ensemble climate‐to‐fish simulations from one Earth System Model (IPSL‐CM6A‐LR) and one Marine Ecosystem Model (APECOSM), this study examines the ToE of epipelagic, migratory and mesopelagic fish biomass alongside their main environmental drivers for two contrasted climate‐change scenarios. Globally averaged biomass signals emerge over the historical period. Epipelagic biomass decline emerged earlier (1950) than mesozooplankton decline (2017) due to a stronger signal in the early 20th century, possibly related to trophic amplification induced by an early emerging surface warming (1915). Trophic amplification is delayed for mesopelagic biomass due to postponed warming in the mesopelagic zone, resulting in a later emergence (2017). ToE also displays strong size class dependence, with epipelagic medium sizes (20 cm) experiencing delayed emergence compared to the largest (1 m) and smallest (1 cm) categories. For the epipelagic and mesopelagic communities, the regional signal emergence lags behind the global average, with median ToE estimates of 2030 and 2034, respectively. This is due to stronger noise in regional time‐series than in global averages. The regional ToEs are also spatially heterogeneous, driven predominantly by the signal pattern akin to mesozooplankton. Additionally, our findings underscore that mitigation efforts (i.e., transitioning from SSP5‐8.5 to SSP1‐2.6 scenario) can potentially curtail emerging ocean surface signals by 30%.